Faktor Penentu Motivasi Dan Kepuasan Kerja Karyawan Di Universitas Muhammadiyah Makassar - Rasulong, Ismail (Universitas Muhammadiyah Makassar, 2011)
The study aims to analyze the direct influence of organizational culture, compensation, organizational commitment, and leadership to motivation and job satisfaction, to analyze the direct influence work motivation to employee job satisfaction, and to analyze the indirect effect of organizational culture, compensation, organizational commitment, and leadership to job satisfaction employees through motivation.Data collected by the census method. The respondents were as many as 53 people who are all permanent employees of the University of Muhammadiyah Makassar. Data collection instruments were questionnaire and data analysis using path analysis.The research concluded that organizational culture has a significant positive direct effect to motivation and job satisfaction, organizational commitment has a positive and significant direct influence to motivation and job satisfaction, work motivation has a significant positive direct effect on job satisfaction, organizational culture has indirect effect is positive and significant impact to job satisfaction through motivation, and organizational commitment had an indirect relationship is positive and significant impact to job satisfaction through motivation.